Childfree Perspektif Psikologi Dan Hukum Islam - Ummu, Ummu Aemanah; Nurrahmah, Fitriya (Fakultas Hukum Universitas Muhammadiyah Cirebon, 2024)
This research aims to determine the psychological problems experienced by couples who decide to be childfree. Couples who decide to be childfree usually assume that whether or not having children is a personal right and human right that cannot be forced by anyone. This research is library research with a psychological approach to find out the reality of couples in deciding to be childfree. as well as a normative approach to understanding childfree law in Islam. From this research it can be found that there are several factors that couples choose to be childfree including economic, mental, personal and personal experience factors, cultural factors and overpopulation. Apart from that, couples who decide to be childfree are significantly less psychologically fulfilled than couples who have children and a woman who has children has a more caring and stable emotional side than those who decide to be childfree. And actually, when a couple chooses to be childfree, there are psychological problems including Social Concern and Relationship Concern. And families who choose to be Childfree will clearly contradict the religious narrative which actually proves the existence of a child in the midst of the family. In the Islamic religion itself, the presence of children can be a bridge for parents to play a role and make important contributions in advancing civilization in the future. Keywords: Childfree, Psychology, Islamic Law